SISTEM INFORMASI PENJUALAN PADA TOKO ELEGANT FURNITURE BATURAJA BERBASIS WEBSITE - Fitra Setiawan, Dimas; Pujianto; Alkodri, M. Nang (Universitas Mahakarya Asia, 2023)
Elegant Furniture Baturaja store located in Baturaja City, South Sumatra is one of the business fields engaged in the sale of furniture products that offer a variety of products and types such as chairs, cabinets, tables, sofas, beds and storage shelves. The promotion and sales process remains the same still directly, meaning that customers must come to the store to buy the desired product. The development of a website-based sales information system at Elegant Furniture Baturaja Store is one of the steps to increase sales and product promotion that can be utilized by the company. The purpose of building a website-based sales information system for furniture sales is so that customers can place orders without having to visit the Elegant Furniture Baturaja Store. The information system is built with the PHP programming language and MySQL database, and uses Visual Studio Code as the editor software. It is expected that the online-based sales information system designed using a website can facilitate customers and improve the sales process of furniture products at the Elegant Furniture Baturaja Store.